Results of a multidisciplinary strategy to improve the management of cardiovascular risk factors after liver transplantation. Issue 8 (25th April 2022) - Sastre, Lydia; García, Raquel; Viñals, Clara; Amor, Antonio J.; Yago, Gema; Hervás, Alicia; Sánchez, Lorena; Trabal, Joan; Molero, Judit; Escudé, Laia; Pagano, Giulia; Blasco, Miquel; et al.
Abstract: Although liver transplantation (LT) recipients are at high cardiovascular risk (CVR), the management of CVR factors (CVRF) after LT is far from optimal and needs to be improved. For this reason, we developed a multidisciplinary protocol to standardize the identification, risk stratification, management, and targets of therapy of CVRF during the first post‐LT year. The grade of identification and control of CVRF 12 months after LT in the postintervention cohort (LT January 2018–January 2020, n = 150) were compared with a control cohort who underwent LT between July 2015 and December 2016 (n = 100). Before LT, the prevalence of metabolic‐associated fatty liver disease as the indication of LT and the presence of obesity were significantly higher in the postintervention cohort, whereas the prevalence of other CVRF and renal dysfunction tended to be higher. Cyclosporine A was used less frequently in the postintervention cohort, whereas everolimus tended to increase. At 12 months after LT, the proportion of patients with measured blood pressure (88% vs. 56%), glycosilated hemoglobin (HbA1c; 96% vs. 72%), and high‐density lipoprotein/low‐density lipoprotein cholesterol (67% vs. 33%) was higher in the postintervention than in the control cohort (all p < 0.001). Blood pressure (64% vs. 36%, p = 0.02) and HbA1c (85% vs. 70%, p = 0.1) were within target in more individuals with hypertension and diabetes mellitus, respectively, in the postintervention cohort. Median total cholesterol levels were lower in the postintervention (184 mg/dl; interquartile range [IQR], 160–210 mg/dl) than in the control cohort (212 mg/dl; IQR, 186–240 mg/dl; p = 0.02). At 2 years after LT, the incidence of cardiovascular events was 14% in the control cohort and 6% in the postintervention cohort ( p = 0.063). In conclusion, a multidisciplinary, multiprofessional strategy can achieve a higher grade of assessment and management of post‐LT CVR despite a worsening metabolic profile of LT recipients.